(untitled) (Eureka Journal of Humanities and Social Research, 2026)
This article provides detailed information about the house museum located in Margilan city, dedicated to the life and work of Jahon Otin Uvaysiy, a prominent representative of Uzbek classical literature and a renowned poetess. The study analyzes the establishment of the museum, its exhibits, manuscripts, and historical sources. It also highlights Uvaysiy’s literary heritage and examines the influence of great poets such as Alisher Navoi and Fuzuli on the formation of her творчество. The article further explores the rare manuscript collections preserved in the museum фонд, their composition, and their scientific significance. This research serves as an important source for a deeper understanding of Uvaysiy’s legacy and for passing it on to future generations.